2018
DOI: 10.1111/jonm.12699
|View full text |Cite
|
Sign up to set email alerts
|

Health care reform in Iran: Implications for nurses’ moral distress, patient rights, satisfaction and turnover intention

Abstract: Health system reform must take into account the concomitant increasing workload and its negative impact in order to ensure that reform does not lead to unintentional detrimental outcomes of increased moral distress, decreased satisfaction and increased turnover rates among nursing personnel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
1
15
0
1
Order By: Relevance
“…O'Connell's study, meanwhile, found that women had a higher moral distress than men [38]. However, the results of some studies have not shown a relationship between gender and experienced moral distress [9,28,30,39].…”
Section: Discussionmentioning
confidence: 98%
“…O'Connell's study, meanwhile, found that women had a higher moral distress than men [38]. However, the results of some studies have not shown a relationship between gender and experienced moral distress [9,28,30,39].…”
Section: Discussionmentioning
confidence: 98%
“…Por lo anterior, es importante que los servicios de salud y el personal directivo consideren a la bioética dentro de sus políticas, organización, normas éticas y otras regulaciones, los cuales resultan útiles para limitar conflictos éticos y estrés laboral en el personal de salud. Las instituciones de salud deben estar comprometidas con mejorar las condiciones de la organización, así como con clarificar y difundir las regulaciones éticas, formar y/o fortalecer a su comité de ética, así como establecer programas de entrenamiento para el manejo del estrés mediante estrategias complementarias como la atención plena, la reflexología, la meditación guiada, además de apoyar a los profesionales de la salud con asesorías para la toma de decisiones bioéticas que no comprometan la salud de los pacientes y limiten el estrés laboral y ético de los trabajadores de la salud (38,39). Otro aspecto importante a considerar es la participación del personal de salud en la integración de comités de ética, en los cuales se expongan los dilemas éticos que podrían tener, con el objetivo consensar la toma de decisiones a partir de los principios de la bioética y lograr una disminución del estrés en los profesionales que, a su vez, determine la calidad del cuidado que estos brindan a sus pacientes (40).…”
Section: Discussionunclassified
“…Indeed, with the implementation of the HSEP and expansion of public health coverage, and the subsequent reduction in treatment tariffs in public centers, referrals to these centers have increased. However, the number of nurses has remained stable, leading to an increased workload for nurses working in public health centers [ 37 , 38 ].…”
Section: Iranian Health Systemmentioning
confidence: 99%